1977
DOI: 10.1212/wnl.27.4.326
|View full text |Cite
|
Sign up to set email alerts
|

Brain lesions that produce delta waves in the EEG

Abstract: Localized delta activity appears in cortex overlying a circumscribed white matter lesion. Less commonly, localized delta activity may result from a localized thalamic lesion. Unilateral diffuse delta activity appears on the side of thalamic or hypothalamic lesions. Bilateral delta activity results from bilateral lesions of the midbrain tegmentum. Localized lesions of the cerebral cortex, unilateral mesencephalic tegmental lesions, and vasogenic edema of the cerebral white matter do not produce delta activity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
230
2
2

Year Published

1981
1981
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 431 publications
(249 citation statements)
references
References 0 publications
15
230
2
2
Order By: Relevance
“…The present findings agree with previous studies in which subcortical damage in mild VaD patients were responsible for a large and widespread increase of theta source activity (Gloor et al, 1977;Coben et al, 1983). Of note, the increase of theta could be linked to the general slowing of the dominant frequency in VaD and this could explain why it is less evident in mild AD.…”
Section: Low Eeg Rhythms In Mild Dementiasupporting
confidence: 93%
“…The present findings agree with previous studies in which subcortical damage in mild VaD patients were responsible for a large and widespread increase of theta source activity (Gloor et al, 1977;Coben et al, 1983). Of note, the increase of theta could be linked to the general slowing of the dominant frequency in VaD and this could explain why it is less evident in mild AD.…”
Section: Low Eeg Rhythms In Mild Dementiasupporting
confidence: 93%
“…In fact, a theoretical model considering a mean speed propagation in white matter fibers of 7.5 m/s (together with other parameters) is associated with a fundamental mode frequency of 9 Hz (Nunez, 1995;Nunez and Srinivasan, 2006), that is, the typical mode of scalp-recorded EEG. It is to be noted that a correlation between white matter damage and widespread slowing of EEG rhythmicity was found in other studies, following the presence of cognitive decline (d'Onofrio et al, 1996;Szelies et al, 1992Szelies et al, , 1999, multiple sclerosis (Leocani et al, 2000), or cerebral tumors (Gloor et al, 1977;Goldensohn, 1979). In the present study, we found neither impact of vascular damage on the IAF, nor significant correlation between CV damage score and IAF.…”
Section: Eeg Frequency Indices Of a Rhythms And CV Damagementioning
confidence: 64%
“…Neurophysiological studies in animals have established a solid connection between pathological delta-wave (1-4 Hz) generation in GM and axonal injuries in WM. Gloor et al showed that polymorphic delta-band slow-waves produced by (white matter) WM axonal lesions in the cat were localized to the GM area of cortex overlying the lesion Gloor et al, 1977). They also found that pathological delta-waves can be induced by the administration of atropine in the WM (Schaul et al, 1978).…”
Section: Clinicalmentioning
confidence: 99%